STUDI MODEL EMBANKMENT TANAH DENGAN CAMPURAN KAPUR-ABU SEKAM PADI DAN SERAT KARUNG PLASTIK - Agus Setyo Muntohar, Anita Widianti, Edi Hartono (Jurnal Teknik Sipil UMS, 2008)
The previous research result has shown that soil stabilization that use lime, rice husk ash and plastic sack fiber is ductile and produces high strength. This research studies the bearing capacity and vertical displacement of embankment models to obtain the highest bearing capacity and the lowest displacement of various configuration of lime-rice husk ash-plastic fiber mixture are compares with that of natural soil embankment. The configuration tested are layered, columned, covered and mixed embankments. Two variations of the base of the embankment model are silt soil and soft clay soil. The study is limited for the case of static loading. The main apparatus is an adjustable displacement rate load cell. Loading is increased slowly such that the rate of displacement is about 1 mm/minute. The loading is ended by the occurance of failure indicated by sudden drop of loading force. The vertical displacement is read from dial gauge indicator. The result of the study indicates that the best mixture in term of highest bearing capacity and lowest displacement is the mixed embankment. The measured ultimate bearing capacity of mixed embankment reach 3625 kPa that is 111 times that of the natural soil embankment. The failure of the natural soil embankment is at 7,0 kN loading. At this loading the measured vertical displacement of mixed embankment is 65 % less than that of the natural soil embankment.